Melacak Jejak Kepengarangan Sastrawan Bali Modern Pra-Kemerdekaan - Purnama, I Gede Gita; Eka Guna Yasa, I Putu (Humanis, 2020)
Modern Balinese literature is one of the fields of classification in the world of Balinese literature. Balinese literary works that were born in the modern era or after the inclusion of foreign cultural influences in Balinese literary works are called modern Balinese literature. At the beginning of its emergence in the pre-independence era, modern Balinese literature was conceived by teacher teachers who served in formal schools established by the Dutch colonial. The early works of these teachers became a milestone in the birth of modern Balinese literature. Narrative texts written by I Made Pasek and Mas Niti Sastro became the initial embryos of Balinese short stories. In the form of some narrative texts they have presented a very modern form, no longer similar to the form of narrative doengeng or folklore. Then in content, the value content offered by the author is a very modern value content, not merely the values ??of tradition.